Development of Assesment Instrument Based on Scientific Literacy in Digestive System, Additives, and Addictive Substances for Junior High School - Yuni Rosa Lina; Helendra Helendra; Fitri Arsih (Bioeducation Journal, 2018)
Success in science education can be seen from the achievement of science literacy learners. The results of the analysis show that the ability of science literacy of learners in Padang City was in low category. This is because the learning process has not been fully support to the development of science literacy skills of learners, especially on the development of science learning assessment instrument. This study aims to produce assessment instruments based scientific literacy on digestive system, additives, and addictive substances for SMP. This research used the research development models by Plomp where consisting of three phase, there are preliminary phase, development or prototype (development or prototyping phase), and assessment phase. The subject were 47 students of SMP Negeri 1 Padang and validator consisted of 3 lecturers of FMIPA. This research resulted in scientific literacy assessment on digestive system, additives, and addictive substances for SMP, those are valid for both logical and empiric, practical in the use for students, high reliability, have good distinguisher, and level of difficulty. Based on logical validity, this scientific literacy assessment declared 80.42% valid by experts. Based on empiric validity, this scientific literacy assessment declared 70.69% valid. Based on practicality, this scientific literacy assessment declared 81,70% by students.